Teaching and assessment of physics measurement uncertainty in remote delivery during Covid-19 Lockdown - Dehipawala, Sunil; Schanning, Ian; Sukmayadi, Dodi; Tremberger, George; cheung, tak (International Journal of Research in STEM Education, 2023)
The teaching and assessment of measurement uncertainty in physics lab class has been an ongoing challenge under the Covid-19 no-access policy, especially in a Two-year community college setting with less budget. The tactile experience as a tacit knowledge must be delivered in words and students are presumed to be able to learn from reading and following the rules in a simulation, with an analogy of the learning of emotions in a literature class with the original words in the novel and the related movies. The transference learning process offers guidance to design the remote delivery of experiential learning in a lab class. The quantitative uncertainty in physics lab is an assessment of how well we know. The misconception that a simulation lab would carry zero uncertainty was found to be the more difficult for students to eliminate. When the teaching of uncertainty percent calculation be classified as a lesson at the average difficulty level, then the teaching of the uncertainty in graphical representation would be deemed to be at the next difficulty level. For the case with a single formula in several variables, the small change concept in algebra can be used to estimate the uncertainty when the small changes are in absolute magnitudes.  For the case with two or more cascade formulas, the use of simulation to estimate uncertainty from the variation of the simulation results would be practical. Teaching uncertainty examples and assessment rubric examples for experiential learning in remote delivery during Covid -19 pandemic are discussed.